The Flow and Pressure Relationships in Different Tubes Commonly Used for Semi-occluded Vocal Tract Exercises - Amarante Andrade, Pedro; Wistbacka, Greta; Larsson, Hans; Södersten, Maria; Hammarberg, Britta; Simberg, Susanna; Švec, Jan G; Granqvist, Svante (Journal of voice, 2016)
This experimental study investigated the back pressure (P(back)) versus flow (U) relationship for 10 different tubes commonly used for semi-occluded vocal tract exercises, that is, eight straws of different lengths and diameters, a resonance tube, and a silicone tube similar to a Lax Vox tube. All tubes were assessed with the free end in air. The resonance tube and silicone tube were further assessed with the free end under water at the depths from 1 to 7 cm in steps of 1 cm. The results showed that relative changes in the diameter of straws affect P(back) considerably more compared with the same amount of relative change in length. Additionally, once tubes are submerged into water, P(back) needs to overcome the pressure generated by the water depth before flow can start. Under this condition, only a small increase in P(back) was observed as the flow was increased. Therefore, the wider tubes submerged into water produced an almost constant P(back) determined by the water depth, whereas the thinner straws in air produced relatively large changes to P(back) as flow was changed. These differences may be taken advantage of when customizing exercises for different users and diagnoses and optimizing the therapy outcome.
Keywords: Equipment Design; hlasové řasy; hlasový trénink; Nonlinear Dynamics; Voice Training; Resonance tube; lidé; tlak; nemoci laryngu; larynx; Vocal Cords; Sound; silikony; zvuk; Semi-occluded vocal tract exercises; Larynx; Laryngeal Diseases; nelineární dynamika; Phonation; Voice; Flow; Silicones; Back pressure; anatomické modely; fonace; Straw; design vybavení; Lax Vox tube; Models, Anatomic; Voice therapy; Pressure; hlas; Humans